A COMPARATIVE EVALUATION OF THERAPEUTIC EFFICACY AND SAFETY OF THE CRYOTHERAPY (LIQUID NITROGEN) WITH TOPICAL 20percent PODOPHYLLIN V/S INTRALESIONAL BLEOMYCIN WITH TOPICAL 5percent PLACENTREX GEL IN THE TREATMENT OF CONDYLOMA ACUMINATA - Mahajan, Bb; Tilak Raj, Rakesh; Raj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Condyloma acuminata is a common sexually transmitted disease of sexually active adults caused by HPV having variable response to the different available therapies and none of them have proved to be uniformly effective as recurrences are common. Objective: A randomized, single blinded, paralleled group, intention to treat prospective study was conducted not only to compare the two treatment modalities but also to determine the efficacy and safety of drugs under study. Materials and Methods: 60 cases of clinically diagnosed condyloma acuminata were randomly divided into two equally matched groups (n=30). Group-I, patients were treated with a combination of cryotherapy (liquid nitrogen) with topical 20percent podophyllin and Group-II, patients were treated with a combination of intralesional bleomycin with topical 5percent placentrex gel. Evaluation criteria included assessment of lesion response, patient's response, duration of response, recurrence rate and safety. Photographic assessment at baseline, 2, 4, 8, 12 and 24 weeks was done. Results: 289 condylomas were treated in total (n=60), 175 (60.55percent) Group-I and 114(39.4percent) in Group-II. 49 patients completed the study, 24 treated in Group-I and 25 in Group-II. By intention to treat, lesional clearance rate at 24 weeks in Group-I was 80percent as compared to 83.33percent in Group-II. The clinical efficacy of combination therapy in Group-II was higher as compared to Group-I but there was no statistically significant difference between both the groups (p greater than0.05). The side effects evaluated in this study were mild and transient and they were assessed using a 4 point clinical score (0=absent, 1=mild, 2=moderate, and 3=severe). Conclusion: In this comparative study Intralesional bleomycin with 5percent placentrex gel was found to be more effective although both treatment modalities have good potential for treatment of condyloma. Key words: Anogenital warts, Liquid Nitrogen, Combination therapy, Intralesional injection, Topical application